A discrete choice experiment on Chinese parents' preferences of vaccine schedules against six childhood infectious diseases - Aodi Huang; Lin Tang; Lifang Huang; Jun Li; Xue Zhang; Jiajie Liu; Yang Zhou; Bingling Zhang; Lei Wang; Qian Zhang; Xia Xu; Zemei Zhou; et al. (Vaccine: X)
Background: China's Expanded Program on Immunization (EPI) provides vaccinations against 12 vaccine preventable diseases (VPDs) at no cost to families. For some VPDs, parents may opt to substitute equivalent non-program vaccines, including combination vaccines, for EPI vaccines; substitute vaccines must be paid for by the family. Although parents have several choices for vaccinating their children, their preferences for vaccines and immunization schedules have not been systematically evaluated. We used a discrete choice experiment to evaluate four attributes of vaccines for routine immunization: number of injections, risk of mild side-effects, out-of-pocket cost, and location of manufacturer (domestic or imported). Methods: In a questionnaire-based survey conducted in vaccination clinics, guardians were asked to select their preferred vaccination schedule from five options in ten choice sets with the four attributes. We used a mixed logit model to determine parental preferences for vaccination schedules, relative importance of attributes, and predict the likelihood of successful vaccination under different scenarios. Results: A total of 581 parents from seven provinces and cities in China participated in the survey, and 488 respondents had internally consistent responses and were included in the analysis. The number of injections in the schedule was the most important attribute for predicting uptake, followed by risk of mild side-effects. Preferences varied by region and parental role. Predicted uptake in the preferred vaccination scenario relative to base-case schedule uptake was a 99.55 % increase. Conclusions: Number of injections and risk of mild side-effects were the two most important attributes of the routine immunization schedule. Results from this study can help optimize the immunization schedule in China to improve coverage of childhood vaccines.